QUANTITATIVE ANALYSIS OF ACETAMINOPHEN AND IBUPROFEN MIXTURE IN TABLET UTILIZING CENTERED AVERAGE ON SPECTRUM RATIO BY SPECTROPHOTOMETRIC TECHNIQUE - Bachri, Muchlisyam; R P, Tuty; R, Edward (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Centered average on spectrum ratio by spectrophotometric technique has been done validated for acetaminophen (ACT) and ibuprofen (IBU) in mixture. The goal of this research is to analyze concurrent determination of ACT and IBU mixture in tablet, using pH 7.2 phosphate buffer and ethanol (91:9) as solvent mixture. Methods: The spectrophotometric technique was made by addition of standard solution from IBU, and the absorption spectrum of each drug has been recorded, which is divided by corresponding concentration as a dividing factor; after that, the centered flat of ratio spectra of ACT and IBU concentrations was determined by calibration graphs with measuring at obtained maximum wavelengths 244 nm for ACT and 221 nm for IBU. Results: The research results showed that linearly correlation acetominophen and IBU are 3.0–9.0 μg/mL and 5.0–13.0 μg/mL, respectively, and linearly regression equations are 1.5800X+0.4809 and 0.0991X+0.0205 with coefficient correlation are 0.9962 and 0.9990. Result of ACT and IBU in local tablet is 100.72±0.12% and 98.82±0.06% with the average of percentage recovery for ACT and IBU is 100.01% and 100.31%, and relative standard deviation value is 0.03% and 0.06% respectively. Conclusion: It can be concluded that centered average on spectrum ratio spectrophotometric technique is a smooth, accelerated, correct, and rigid for the analysis of ACT and IBU in mixture.